Gas exchanges and growth of passion fruit under saline water irrigation and H2O2 application - Elysson M. G. Andrade; Geovani S. de Lima; Vera L. A. de Lima; Saulo S. da Silva; Hans R. Gheyi; André A. R. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The study was carried out to evaluate the photosynthetic efficiency and growth of yellow passion fruit, cultivated under different levels of irrigation water salinity and exogenous application of hydrogen peroxide. The experiment was carried out in greenhouse of the Universidade Federal de Campina Grande, PB, Brazil, using drainage lysimeters with capacity for 100 dm3, filled with Entisol of sandy texture. The experimental design was randomized blocks using a 4 x 4 factorial scheme, with three repetitions, corresponding to four water salinity (0.7; 1.4; 2.1 and 2.8 dS m-1) and four concentrations of hydrogen peroxide (0, 20, 40 and 60 µM). The different concentrations of hydrogen peroxide were applied by soaking the seed for a period of 24 h and spraying the leaves on the adaxial and abaxial sides. At 35 days after transplanting, the interaction between water salinity and hydrogen peroxide concentrations did not significantly interfere with plant physiology and growth, except for the number of leaves. The hydrogen peroxide did not cause significant effects on any of the evaluated plant variables. Increasing salinity of irrigation water led to reduction in gas exchanges at 61 and 96 days after transplanting. Water salinity inhibited the CO2 assimilation, transpiration, stomatal conductance, instantaneous carboxylation efficiency and stem diameter of passion fruit plants.